UAV formation with digital cameras (II) - Akilan, K. (2017)
This research paper would go about the basics of objection detection and the coding details implemented. Object detection would be done through stereo matching and depth to line extraction. The whole project was carried out on Ubuntu Robot Operating System (ROS) platform and experimented on Matrix Laboratory (MATLAB) as well. Details on the following process upon completion of this stage would also be explained. Moreover, it will touch on topics such a SLAM. Various SLAM platforms would also be tested out like ORB Slam and Open Slam to determine the better platform and work forth. The main bulk of the project went about, assisting a research study at the same time doing the necessary coding to implement the program and test it. Calibrations of the camera were also involved in reducing errors when information acquired.